Teacher Trainees’ Perspectives on Storytelling in Primary EFL Classrooms: The Case of Online Training to Tell Stories Effectively - Çelik Korkmaz, Şule (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
The COVID-19 pandemic has obliged EFL teacher trainers to find new pathways to prepare teacher trainees (TTs) for future classrooms. For the TTs enrolled in the Teaching English to Young Learners (TEYLs) course, telling stories effectively is of utmost important. Thus, this study aimed to investigate the TTs’ perspectives on creating and telling storybooks in EFL primary classrooms besides the necessity for being trained to tell stories effectively via their out-of-class video-recorded microteaching sessions. The data were collected via the questionnaire and the focus group interviews. The findings revealed: (1) the TTs approved the necessity of creating and telling stories in primary EFL classrooms, which indicates their developed cognition regarding the pedagogical advantages of telling stories to children; (2) effective and interactive storytelling skills were associated with the story teller’s narration skills, tone of voice, mimicry, gesture, and interaction skills; (3) the TTs were more in favor of the necessity for being trained to tell a story effectively through face-to-face education than through online education despite reporting several pros and cons of both ways; (4) female TTs were more in favour of creating story books and the necessity for being trained to tell a story effectively via face-to-face training.